Immunohistochemistry and spinal projections of the reticular formation in the northern leopard frog, Rana pipiens - Adli, D.S.H.; Cruce, W.L.R.; Stuesse, S.L. (1999)
Over 30 nuclei have been identified in the reticular formation of rats, but only a small number of distinct reticular nuclei have been recognized in frogs. We used immunohistochemistry, retrograde tracing, and cell morphology to identify nuclei within the brainstem of Rana pipiens. FluoroGold was injected into the spinal cord, and, in the same frogs, antibodies to enkephalin, substance P, somatostatin, and serotonin were localized in adjacent sections. We identified many previously unrecognized reticular nuclei. The rhombencephalic reticular formation contained reticularis (r.) dorsalis; r. ventralis, pars alpha and pars beta; r. magnocellularis; r. parvocellularis; r. gigantocellularis; r. paragigantocellularis lateralis and dorsalis; r. pontis caudalis, pars alpha and pars beta; nucleus visceralis secundarius; r. pontis oralis, pars medialis and pars lateralis; raphe obscurus; raphe pallidus; raphe magnus; and raphe pontis. The mesencephalic reticular formation contained locus coeruleus-subcoeruleus, r. cuneiformis, r. subcuneiformis, raphe dorsalis-raphe centralis superior, and raphe linearis. Thus, the reticular formation of frog, which is an anamniote, is organized complexly and is similar to the reticular formation in amniotes. Because many of these nuclei may be homologous to reticular nuclei in mammals, we used mammalian terminology for frog reticular nuclei. (C) 1999 Wiley-Liss, Inc.